1999
DOI: 10.1038/sj.ejhg.5200248
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous spectrum of mutations in the Fanconi anaemia group A gene

Abstract: http://www.stockton-press.co.uk/ejhg deletions was detected, which removed between 1 and 30 exons from the gene. Most microdeletions and insertions occurred at homopolymeric tracts or direct repeats within the coding sequence. These features have not been observed in the other FA gene which has been cloned to date (FAC) and may be indicative of a higher mutation rate in FAA. This would explain why FA group A is much more common than the other complementation groups. The heterogeneity of the mutation spectrum a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
93
0
2

Year Published

1999
1999
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(97 citation statements)
references
References 21 publications
2
93
0
2
Order By: Relevance
“…This equates to a detection rate of 97% using the methodology described here, contrasting strongly with the situation in FANCA, where frequent partial deletions make mutation analysis difficult. 18,19 The majority of the mutations described are expected to yield truncated FANCG proteins varying from 7% to 95% of the wild type 68 kD. FANCG is known to form a complex with FANCA, and it has been shown that this binding is due to sequences both in the amino terminal and the carboxy terminal ends of the protein 20 (Kuang et al, 2000 personal communication).…”
Section: Discussionmentioning
confidence: 99%
“…This equates to a detection rate of 97% using the methodology described here, contrasting strongly with the situation in FANCA, where frequent partial deletions make mutation analysis difficult. 18,19 The majority of the mutations described are expected to yield truncated FANCG proteins varying from 7% to 95% of the wild type 68 kD. FANCG is known to form a complex with FANCA, and it has been shown that this binding is due to sequences both in the amino terminal and the carboxy terminal ends of the protein 20 (Kuang et al, 2000 personal communication).…”
Section: Discussionmentioning
confidence: 99%
“…22 Five changes were novel missense mutations leading to nonconservative amino-acid substitutions in four cases, none of which was present in 79 normal controls. One additional missense mutation A3982G (causing the aminoacid change T1328A) had previously been reported to be pathogenic, 23 and the other seven nucleotide changes were polymorphisms. A recent analysis of FANCC in 97 cases of sporadic pediatric AML found no evidence of known pathogenic mutations, although one polymorphic variant was present at four-fold greater frequency in the AML cases compared to controls.…”
Section: Introductionmentioning
confidence: 99%
“…We selected the FANCA gene for analysis since mutations in this gene account for 70% of all cases of FA. The mutation profile of FANCA is highly heterogeneous with over 100 different mutations described, 23,[27][28][29] and there is a 40% incidence of large deletions, which remove 1-43 exons from the gene. 28,30 Screening for these mutations thus accounts for nearly 30% of all FA mutations across all complementation groups.…”
Section: Introductionmentioning
confidence: 99%
“…The SSCP analysis on genomic DNA was identical to that used in a study on FA patients (Wijker et al, 1998). This study shows that the method is able to identify mutations and polymorphisms.…”
Section: Discussionmentioning
confidence: 79%
“…Genomic DNA from eight tumours was also tested in an exonby-exon SSCP analysis described elsewhere (Wijker et al, 1998). The 43 exons of FAA (Lanzano et al, 1997) were amplified from genomic DNA with primers located 40Ð60 bp from the exon boundaries with T7 (sense) and Sp6 (antisense) sequences to facilitate sequencing.…”
Section: Mutation Screeningmentioning
confidence: 99%